Transformasi Pembelajaran PAI Melalui Media Sosial: Strategi Meningkatkan Keterlibatan Mahasiswa - Chairul Huda; Muhammad Zaki (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Digital transformation in the modern era has significantly influenced various aspects of life, including education. Today's university students, as digital natives, have a strong tendency to access information and learn through social media platforms such as Instagram and YouTube. This opens up great opportunities to develop more adaptive, contextual, and relevant learning strategies, particularly in Islamic Religious Education (PAI), which is often perceived as traditional and monotonous. This community service project aims to transform PAI learning methods through the integration of social media to enhance student engagement and learning motivation. The implementation method includes five stages: socialization, training and workshops, content production mentoring, instructional implementation, and evaluation and reflection. The results show that the use of YouTube and Instagram as learning media effectively increases student engagement scores (average 3.75) and learning motivation (average 3.80), with YouTube contributing the most by providing long-form, flexible educational content. Instagram complements this by delivering moral messages in a quick and visually appealing format. Beyond improving learning effectiveness, this initiative also promotes Islamic digital literacy and empowers students as content creators for moderate and educational Islamic messages. In conclusion, the strategic integration of social media in PAI learning is a proven innovative approach that should be widely adopted in higher education environments.